Integration of Edge Computing in Mobile Library Services - Dinakaran, S. Samson; Satish, R.; Sujatha, S.; RiadHwsein, Ramee; Mamatjonovich, Mamataliev Marufjon; Tanwani, Shilpi Nishant (Indian Journal of Information Sources and Services, 2026)
The possibility of including edge computing in mobile library systems is an excellent chance to streamline resource-constrained settings in data processing, user access, and real-time information retrieval. Other operational issues, such as limited access to the internet, excessive lag, and dependency on a centralized cloud platform, are some of the challenges that such mobile libraries have to deal with. Using edge computing, data processing may be run on mobile units or on edge computing devices nearby, therefore minimizing the time of accessing the remote server and remote units. In this paper, a framework for incorporating edge computing into a mobile library will be provided, enabling digital lending, real-time user catalog updates, user behavioral data analytics, and the delivery of contextual content. Moreover, the architecture includes edge nodes to provide caching, data filtering, and lightweight analytics, which will guarantee the continuity of library services in rural or disaster-affected areas with a constrained bandwidth. These findings indicate increased system performance, reduced delays, and improved responsiveness to abrupt alterations in user requirements. This not only helps bridge the digital divide in these areas but also creates sophisticated, sustainable, scalable, and innovative library services. These results suggest the potential of edge-aided mobile libraries as decentralized public information hubs, facilitating the transition to adaptable and multifaceted public information systems.